Kunskapshistoria, idéhistoria och annan historia: En översikt i skandinaviskt perspektiv - Simonsen, Maria; Jansson, Anton (Slagmark - Tidsskrift for idéhistorie, 2020)
History of knowledge, history of ideas, and other forms of history: An overview in Scandinavian perspective This article is an overview in which we paint a picture of the research field that during the 2010s has emerged under the banner of history of knowledge. The purpose is to complement the preface of this special issue, and so give a better context for the issue, by providing a somewhat broader introduction. History of knowledge is here specifically related to history of science and history of ideas. In the first half of the text, we present the emergence of the field and some of its key concepts and perspectives, as well as some critique it has faced. In the second half, we discuss and compare history of knowledge with the institutionalised disciplines of history of ideas in Scandinavia. We see some clear overlaps and similarities between history of ideas and history of knowledge, but also differences. For instance, historians of ideas study traditions of thought, which not necessarily count as knowledge. One point we see with history of knowledge as a field is how it works as an interdisciplinary and integrative meeting point, where historical researchers from different disciplines can gather to discuss the appearance and social function of knowledge, and by doing this have the possibility of also generating new perspectives on cultural and societal history.